Proclamation 10846-Critical Infrastructure Security and Resilience Month, 2024 October 31, 2024 - Biden, Joseph R (Daily Compilation of Presidential Documents, 2024)
Through my American Rescue Plan, Bipartisan Infrastructure Law, Inflation Reduction Act, and CHIPS and Science Act, we are investing billions of dollars to secure and bolster our infrastructure. The partnership will advance United States economic and national security interests by strengthening our shipbuilding and industrial capacity while simultaneously opening up new trade routes and pushing back against foreign aggression and bolstering our international alliances. Subjects: Arctic and polar icebreaker shipbuilding, international cooperation; Climate change; Climate resilience, improvement efforts; Critical Infrastructure Security and Resilience Month; Critical infrastructure, strengthening efforts; Cybersecurity, strengthening efforts; Group of Seven (G–7) nations; Infrastructure development, international assistance for developing countries; Infrastructure improvements; Natural disasters, climate change impacts; North Atlantic Treaty Organization.